2019
DOI: 10.1111/ocr.12268
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for genes that shape human faces: Initial successes and challenges for the future

Abstract: Structured Abstract There is ample evidence from heritability studies, genetic syndromes and experimental animal models that facial morphology is strongly influenced by genes. In this brief review, we present an up‐to‐date overview of the efforts to identify genes associated with the size and shape of human facial features. We discuss recent methodological advances that have led to breakthroughs, but also the multitude of challenges facing the field. We offer perspective on possible applications of this line o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…We then queried whether any genes within 0.25 Mb of the SNP or genome scan LOD peaks are known to be associated with craniofacial development or phenotypes (Table 3). As with human facial shape GWAS [42], LOD peaks tended to be located in non-coding regions. While the focal genes we identified all have known roles in skeletal or craniofacial development, they also tend to be developmentally ubiquitous.…”
Section: Association Mappingmentioning
confidence: 94%
See 1 more Smart Citation
“…We then queried whether any genes within 0.25 Mb of the SNP or genome scan LOD peaks are known to be associated with craniofacial development or phenotypes (Table 3). As with human facial shape GWAS [42], LOD peaks tended to be located in non-coding regions. While the focal genes we identified all have known roles in skeletal or craniofacial development, they also tend to be developmentally ubiquitous.…”
Section: Association Mappingmentioning
confidence: 94%
“…Quantitative genetics analyses [32,36,37] as well as expression and epigenomic atlases of facial development both strongly point to the potential for hundreds or thousands of genetic loci with as-yet-undetected QTL variance contributions [38][39][40]. Increased sample sizes, greater mapping resolution, and the development of new experimental lines all have the potential to expand the facial shape QTL library and increase the precision of variant localization [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in 364 height‐related SNPs. Rather than including loci from new GWAS studies, for example for human facial variation (reviewed by Weinberg et al, 2019), we restricted our studies to those used by Sheehan and Nachman (2014) to ensure comparability between these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Significant progress has been made in elucidating the genetic basis of human facial traits 1 3 . Genome-wide association studies (GWASs) have identified and replicated numerous common genetic variants associated with normal-range facial morphology 4 13 (see implicated genes by facial regions in Fig S1 ); yet these variants cumulatively explain only a small fraction of the heritable phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%